An optimization model of economic order quantity with financial constraints and market tolerance in ud plastikq. (April 2020) - Larasati, R H; Khabibah, S; Aziz, A
Abstract: An optimization model of Economic Order Quantity (EOQ) is one of the methods used to determine the inventory order quantity that can minimize the cost of storage and the cost of ordering supplies. The optimization model in this paper is an optimization model of Economic Order Quantity (EOQ) with financial constraints and market tolerance. Financial constraints include the limited capital available per period and the advanced payment. In the market tolerance factor, there are two periods of market tolerance and three levels of the backorder. Based on this model, numerical simulations can be formulated and carried out so that the best optimal solution was obtained when conditions are unlimited, complete backorder, no advanced payment and the market tolerance period is 0.2 with a total cost decrease of 28, 92% and a total profit increase of 13, 37% from the initial condition.